Impact of the Perceived Mental Stress During the COVID-19 Pandemic on Medical Students' Loneliness Feelings and Future Career Choice: A Preliminary Survey Study - Zheng, Qiuyue; Lin, Xianhao; He, Lin; Freudenreich, Thomas; Liu, Tao (Frontiers in Psychiatry, 2021)
The outbreak of the COVID-19 epidemic continues to unfold globally, and its negative impact on the public’s mental health is starting to reveal. Serving as reserve talents for the healthcare system, medical students are not yet professionally matured enough to face one of the worst global public health crises. This may exert increased mental stress and loneliness, which in turn negatively influence medical students’ future career choice. To address the issue, we conducted three online survey studies investigating how the epidemic affects the mental health as well as career attitude of medical students in China during the COVID-19 pandemic outbreak. The results revealed preliminary evidence showing that the perceived stress induced by the COVID-19 epidemic might negatively affect medical students’ future career choice, and the feeling of loneliness may play a mediating role. This study invites more attention to medical students’ mental health during severe public health crisis such as the COVID-19 pandemic.